Design and Development of a Simulator for Modelling Carbon Nanotube - Farhana, Soheli; Alam, A. H. M. Zahirul; Motakabber, S. M. A.; Khan, Sheroz (IOP Publishing, 2013)
In this paper, a Matlab simulator is developed for modelling of carbon Nanotubes (CNTs). First electronics structure is derived and discussed to facilitate the analysis and modelling of the simulator. Then a calculation is done for electron energy dispersion relations for single-wall zigzag CNTs with different tube indexes. From the analysis of energy dispersion relation, it is derived an analytical models for CNT parameters such as the mobility and the intrinsic carrier concentration. Once obtain the CNT parameters, and then import them to the developed simulator. The simulator is based on the semiconductor equations and quantum effects. Finally the simulator produces the result for optimum modelling of CNT for electronic device application